Residual soil-applied zinc improves grain zinc nutritional quality of maize grown under contrasting soil types in Malawi - Botoman, Lester; Nalivata, Patson C.; Chimungu, Joseph G.; Bailey, Elizabeth H.; Munthali, Moses W.; Ander, E. Louise; Mossa, Abdul-Wahab; Lark, R. Murray; Broadley, Martin R. (Frontiers in Soil Science, 2025)
IntroductionA proper understanding of the residual value of zinc (Zn) is essential for sustainable biofortification of food crops. This study hypothesized that Zn applied at rates higher than the current national recommendation would have significant residual benefits on maize productivity and Zn uptake.MethodsThe residual effects of soil-applied Zn on maize grain Zn concentration and uptake were evaluated at two Malawian agricultural research stations, Chitedze and Chitala, each with Lixisols and Vertisols soil types. The experiment used three Zn fertilizer rates (1, 30, and 90 kg Zn ha-1) applied as ZnSO4.7H2O in the previous season, arranged in a randomized complete block design (RCBD) with 10 replications per site. Maize grain yield, and Zn concentrations in grain and stover were measured at harvest. Data were analyzed to assess crop yield and Zn uptake relative to Zn application rates and soil types.ResultsMaize grain yield in the second season was 24.6% higher on plots receiving 30 kg Zn ha-1 compared to those with 1 kg Zn ha-1. Grain Zn concentration and Zn uptake increased by 12.5% and 29.6%, respectively, on plots with 30 kg Zn ha-1 versus the lowest rate. Application of 90 kg Zn ha-1 did not provide additional benefits over 30 kg ha-1 for yield, Zn concentration, or Zn uptake. Residual Zn benefits did not vary between soil types.DiscussionThese results demonstrate that residual application of 30 kg Zn ha-1 significantly enhances maize productivity and Zn biofortification compared to the current national recommendation of 1 kg Zn ha-1. Given no added advantage with 90 kg Zn ha-1, revising Zn fertilizer guidelines to higher but optimized rates could improve the effectiveness of biofortification programs without environmental or economic drawbacks.